Melayani Dunia tanpa Menjadi Duniawi - Maria Patricia Tjasmadi; Immanuel Sukardi; Rinawaty Rinawaty (Sekolah Tinggi Teologi Torsina Surakarta, 2022)
The task of a servant of God is to carry out two divine mandates at once, the spiritual mandate of salvation and the social mandate of development. Based on the initial study, there were many problems faced by God's servants in service, related to economic, emotional, and spiritual formation, which are serious problems faced by the world community as a result of the Covid-19 pandemic. The church as an institution, or God's servants as implementers of the divine mandate, is required to reformulate the service model that is relevant to the pandemic situation, during or after it. This study aims to examine how to serve the world without being